Vitamin D receptor gene polymorphism and serum vitamin D level as risk factors for acquiring Type II diabetes mellitus: VD receptor gene polymorphism and Type II diabetes mellitus - Mohammed, Maryam Salih; Ahmed Jaff, Basima Sadiq; Aziz, Sadat Abdulla (Cellular and Molecular Biology, 2023)
The studies on the relationship between type 2 diabetes mellitus (T2DM) risk and vitamin D receptor (VDR) gene polymorphisms are still inconclusive. Therefore, the objective of the study was to assess possible risks of acquiring T2DM due to polymorphisms in the VDR gene or abnormal serum levels of VD. 362 participants (181 T2DM patients and 181 healthy controls) from the Diabetic Center, Sulaimaniyah/Iraq, from December 2020 to May 2021 were volumtarily enrolled in the study. For each participant, HbA1c, fasting blood sugar (FBS), serum cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglyceride (TG), markers of calcium homeostasis, alkaline phosphatase (ALP), phosphorus, VD and insulin were measured. In addition, FokI, TaqI, ApaI, and BsmI genotypes were also performed using Polymerase Chain Reaction (PCR). The results showed that VD level was significantly lower in T2DM compared to the control group. While, HbA1c was significantly higher in T2DM than in the control group. In contrast to AA (P=0.034) and CC (P=0.011) genotype of ApaI (rs7975232) gene polymorphism, which were dominant among the control group, AC-genotype was significantly (P=0.0001) dominat among T2DM group. Meanwhile, TT-genotype of TaqI (rs731236) was significantly (P=0.05) dominant among control group. While there were not any significant differences between other genotypes among T2DM and control groups. In conclusion, low VD-level is a possible risk factor for developing T2DM, and an association was found, especially between ApaI genotypes and T2DM.